ANALISIS PENGARUH PERTUMBUHAN EKONOMI, UPAH MINIMUM, DAN TINGKAT PENGANGGURAN TERHADAP PENDUDUK MISKIN DI KABUPATEN BENGKAYANG: ANALISIS PENGARUH PERTUMBUHAN EKONOMI, UPAH MINIMUM, DAN TINGKAT PENGANGGURAN TERHADAP PENDUDUK MISKIN DI KABUPATEN BENGKAYANG - Ery Niswan; Ricola Dewi Rawa; Dami (Prodi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Panca Bhakti, 2021)
ABSTRACT One of the goals of national development is to improve economic performance in order to be able to create jobs and organize a decent life for all people which in turn will realize the welfare of the Indonesian population. One of the national development goals is to reduce poverty. Poverty is one of the fundamental problems that is the center of attention of the government in any country. Poverty is a condition in which a person cannot enjoy all kinds of choices and opportunities in fulfilling his basic needs, such as not being able to meet health, decent living standards, freedom, self-esteem and a sense of respect like other people. Poverty is one of the problems in a complex and multidimensional economy. Therefore, it is necessary to find a solution to overcome the problem of poverty. The aims of this study are: (1) To analyze the rate of economic growth and the minimum wage of Bengkayang Regency. (2) To determine the unemployment rate among the poor in Bengkayang Regency. This research will be conducted from October 2020 to December 2020. The research method used is quantitative research using panel data, the data used are time series (2018-2019) and cross section. The regression method used is the multiple linear regression method (Ordinary Least Square). The type of data used in this study is secondary data obtained from the Central Statistics Agency (BPS) and journals as supporters. The results showed that the variable economic growth had a negative and significant effect on poverty, the minimum wage had a positive and significant effect on poverty, open unemployment had a negative and significant effect on poverty. Keywords: Economic Growth, Minimum Wages, Unemployment, and the Poor